2023
DOI: 10.3390/jcm12072509
|View full text |Cite
|
Sign up to set email alerts
|

Carotid–Femoral Pulse Wave Velocity Could Be a Marker to Predict Cardiovascular and All-Cause Mortality of Hemodialysis Patients

Abstract: Among hemodialysis (HD) patients, cardiovascular disease (CVD) is recognized as a major contributor to the high risk of mortality, and emerging evidence has ascertained arterial stiffness as an independent predictor of adverse cardiovascular (CV) outcomes. We aimed to investigate the efficacy of arterial stiffness measurement in predicting CV and all-cause mortality in patients on HD (n = 130). Carotid–femoral pulse wave velocity (cfPWV) was measured by a validated tonometry system. A cfPWV of >10 m/s was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Firstly, the main outcome measured in our study was the change in cfPWV. Although cfPWV has been accepted as a standard tool for the assessment of arterial stiffness [31,32] and has been shown by a recent study to be an independent predictor of all-cause and cardiovascular mortality in patients with chronic HD patients [32], it is still a surrogate endpoint and not a hard clinical outcome. Therefore, the impact of vitamin K supplementation on clinical outcomes should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the main outcome measured in our study was the change in cfPWV. Although cfPWV has been accepted as a standard tool for the assessment of arterial stiffness [31,32] and has been shown by a recent study to be an independent predictor of all-cause and cardiovascular mortality in patients with chronic HD patients [32], it is still a surrogate endpoint and not a hard clinical outcome. Therefore, the impact of vitamin K supplementation on clinical outcomes should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Besides diabetes and high blood pressure, patients having chronic kidney disease (CKD) also possess non-traditional, kidney-specific CV risk factors, including chronic inflammation, albuminuria, disturbed calcium and phosphorus homeostasis, uremic toxins, oxidative stress, and vascular calcifications [2,5]. Many studies have identified several factors that potentially predict adverse CV outcomes and overall survival of patients on maintenance hemodialysis (HD), including vascular status (aortic stiffness, ankle-brachial index, and extent of abdominal aorta calcification) [6][7][8], nutrition markers (albumin, creatinine, and lipid profiles) [9], and serum levels of galectin-3 [10], sclerostin [11], and uremic toxins (p-cresol sulfate, indoxyl sulfate, and carboxymethyllysine) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%